2007
DOI: 10.1016/j.apcatb.2007.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The selective reduction of NO with propene on Pt-beta catalyst: A transient study

Abstract: The mechanism of the NO/C3H6/O2 reaction has been studied on a Ptbeta catalyst using transient analysis techniques. This work has been designed to provide answers to the volcano-type activity behaviour of the catalytic system, for that reason, steady state transient switch (C 3 H 6 /NO/O 2 → C 3 H 6 /Ar/O 2 , C 3 H 6 /Ar/O 2 → C 3 H 6 /NO/O 2 ; C 3 H 6 /NO/O 2 → Ar/NO/O 2 , Ar/NO/O 2 → C 3 H 6 /NO/O 2 ; C 3 H 6 /NO/O 2 → C 3 H 6 /NO/Ar and C 3 H 6 /NO/Ar → C 3 H 6 /NO/O 2 ) and Thermal Programmed Desorption (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Further, this switch evinces that the kinetics of the hydrocarbon combustion reaction are faster than those of NO oxidation and that both NO and C 3 H 6 are involved in the production of partially oxidized hydrocarbon species. These species are believed to play a crucial role in the occurrence of the HC-SCR reaction, as it has been proposed in previous reports. , In essence, all these observations are confirmed by the reverse (NO/C 3 H 6 /Ar → NO/C 3 H 6 /O 2 ) switch.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Further, this switch evinces that the kinetics of the hydrocarbon combustion reaction are faster than those of NO oxidation and that both NO and C 3 H 6 are involved in the production of partially oxidized hydrocarbon species. These species are believed to play a crucial role in the occurrence of the HC-SCR reaction, as it has been proposed in previous reports. , In essence, all these observations are confirmed by the reverse (NO/C 3 H 6 /Ar → NO/C 3 H 6 /O 2 ) switch.…”
Section: Resultssupporting
confidence: 80%
“…A 2 wt % Pt/fMWCNT catalyst was selected to study the surface state of a working HC-SCR catalyst by means of a transient technique. Details of the preparation, characterization, and evaluation of this catalyst as well as of the gas switching apparatus used in this study can be found elsewhere. Given that the feasibility of using fMWCNT-supported PGMs as HC-SCR catalysts is fully contingent on the ability of the carrier to withstand exposure to oxidizing conditions during operation, experiments were undertaken to validate the use of fMWCNTs as a support for HC-SCR catalysts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first reports on selective catalytic reduction of NO by hydrocarbons (HC-SCR) [1,2], extensive research into the HC-SCR applications for the control of NO x in exhaust gases of diesel and lean-burn engines has been carried out [3][4][5][6][7][8][9]. For the practical application of the HC-SCR, an active catalyst capable of reducing NO in large space velocity at ca.…”
Section: Introductionmentioning
confidence: 99%